Eukaryotic translation initiation factor 4All contributes to microRNA-122 regulation of hepatitis C virus replication - Ahmed, Choudhary-Shoaib; Winlow, Poppy L.; Parsons, Aimee L.; Jopling, Catherine L. (Oxford University Press, 2018)
Hepatitis C virus (HCV) is a positive sense RNA virus that persistently infects human liver, leading to cirrhosis and hepatocellular carcinoma. HCV replication requires the liver-specific microRNA-122 (miR-122). In contrast to canonical miRNA-mediated repression via 3’UTR sites, miR-122 positively regulates HCV replication by a direct interaction with the 5’ untranslated region (UTR) of the viral RNA. The protein factor requirements for this unusual miRNA regulation remain poorly understood. Here, we identify eIF4AII, previously implicated in miRNA-mediated repression via 3’UTR sites, as a host factor that is important for HCV replication. We demonstrate that eIF4AII interacts with HCV RNA and that this interaction is miR-122-dependent. We show that effective miR-122 binding to, and regulation of, HCV RNA are reduced following eIF4AII depletion. We find that the previously identified HCV co-factor CNOT1, which has also been implicated in miRNA-mediated repression via 3’UTR sites, contributes to regulation of HCV by eIF4AII. Finally, we show that eIF4AI knockdown alleviates the inhibition of HCV replication mediated by depletion of either eIF4AII or CNOT1. Our results suggest a competition effect between the eIF4A proteins to influence HCV replication by modulation of miR-122 function.